Awareness of and attitude towards HPV and its vaccines among market women in Bodija market. Ibadan. (2016)
BACKGROUND Cervical cancer, commonest among cancers of the female genital tract continued to pose major challenge to women of reproductive age in developing countries though infection by its causative agent, human papilloma virus (HPV) is preventable. This study aimed to assess awareness and attitude of market women concerning HPV and its vaccines in prevention of cervical cancer. MATERIALS AND METHODS A cross sectional study involving 329 market women, using multistage sampling technique. Instrument was an Interviewer--administered questionnaire on socio-demographic characteristics, knowledge and awareness of HPV and its vaccine, sexual history and attitude towards HPV vaccines. Data analysis was done using SPSS version 20.0 with statistical significance level set at p<0.05. RESULTS Mean age of respondents was 29.49±3.65 years. All respondents were sexually active with majority (94.8%) having multiple sexual partners. Awareness of HPV vaccine and Pap smear test was among 1.2% and 9.4% respectively. Attitude towards HPV vaccination was good in 304 (92.4%) with 302 (91.8%) willing to take the HPV vaccines. There was significant association between attitude towards HPV vaccine and willingness to take HPV vaccine CONCLUSIONS Awareness of HPV and its vaccines is low among market women in our community. Policies and actions to step up information dissemination are urgently needed in order to stem the scourge of cervical cancer in our society.